PENERAPAN FORUM REI SITAE DALAM GUGATAN BERDASARKAN PERBUATAN MELANGGAR HUKUM - Ilhami Ginang Pratidina (Universitas Airlangga, 2015)
Forum rei sitae is an embodiment of the jurisdiction in rem, that is the state control over fixed objects or immovable property which is located in the state’s territory. It’s became a habit and jurisprudence in Indonesia that the lawsuit based on tort concerning a dispute over fixed objects, such as land and buildings, suited to the court whose jurisdiction covers an area of fixed objects, based on forum rei sitae as stipulated in Article 118 paragraph (3) Het Herziene Inlandsh Reglement (HIR). However, the truth of that customs and jurisprudence is still questionable. For this reason, this paper seeks to elaborate on whether the forum rei sitae may be applies in a lawsuit based on tort, using statute approach, conceptual approach and take some decision of the judiciary from Indonesian and foreign to strengthen the argument of this paper. Lawsuit based on tort is lead to jurisdiction in personam, while forum rei sitae used in jurisdiction in rem, so the application of forum rei sitae in lawsuit based on tort can’t be justified.